Antibacterial Activity of Leukocyte- and Platelet-Rich Plasma: An In Vitro Study. (27th June 2018) - Cieślik-Bielecka, Agata; Bold, Tadeusz; Ziółkowski, Grzegorz; Pierchała, Marcin; Królikowska, Aleksandra; Reichert, Paweł
Abstract : The aim of the study was to investigate the leukocyte- and platelet-rich plasma (L-PRP) antimicrobial activity. The studied sample comprised 20 healthy males. The L-PRP gel, liquid L-PRP, and thrombin samples were tested in vitro for their antibacterial properties against selected bacterial strains using the Kirby-Bauer disc diffusion method. Two types of thrombin were used (autologous and bovine). Zones of inhibition produced by L-PRP ranged between 6 and 18 mm in diameter. L-PRP inhibited the growth of Staphylococcus aureus (MRSA and MSSA strains) and was also active against Enterococcus faecalis and Pseudomonas aeruginosa . There was no activity against Escherichia coli and Klebsiella pneumoniae . The statistically significant increase of L-PRP antimicrobial effect was noted with the use of major volume of thrombin as an activator. Additionally, in groups where a bovine thrombin mixture was added to L-PRP the zones of inhibition concerning MRSA, Enterococcus faecalis, and Pseudomonas aeruginosa were larger than in the groups with autologous thrombin. Based on the conducted studies, it can be determined that L-PRP can evoke in vitro antimicrobial effects and might be used to treat selected infections in the clinical field. The major volume of thrombin as an activator increases the strength of the L-PRP antimicrobial effect.